The Boo-Boos of Bluebell Elementary - Wallace, Chelsea Lin; Farrell, Alison, 1979- (San Francisco : Chronicle Books, 2023)
"Whether it is a splinter, a stomachache, or a loose tooth, the children at Bluebell Elementary know to go to Miss P to fix their bumps and bruises."--
Ages 5 to 8.
Grades K-1.
Keywords: Nurses -- Juvenile fiction; Wounds and injuries -- Juvenile fiction; School nursing -- Juvenile fiction; Elementary schools -- Juvenile fiction; Nurses -- Fiction; Wounds and injuries -- Fiction; School nursing -- Fiction; Elementary schools -- Fiction; Schools -- Fiction; Stories in rhyme; Picture books